2022
DOI: 10.7717/peerj.13825
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and behavioral studies reveal differences in olfaction between winter and summer morphs of Drosophila suzukii

Abstract: Spotted-wing drosophila, Drosophila suzukii (Matsumura), is a major economic pest of several fruit crops in Europe, North and South America, and other parts of the world because it oviposits in ripening thin-skinned fruits. This vinegar fly exhibits two distinct morphotypes: a summer and a winter morph. Although adaptations associated with the winter morph enhance this invasive pest’s capacity to survive in cold climates, winter is still a natural population bottleneck. Since monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Additionally, monitoring traps are less efficient during the winter, which could be associated with differences in the response to volatiles between SM and WM [55]. Schwanitz et al (2022) found several differentially expressed genes between SM and WM associated with the olfactory behavior of D. suzukii, namely those linked to food-seeking and mating behaviors, reinforcing previous work that suggested that WM flies have different food preferences than SM [56,57]. Considering that the flies surviving the winter are the most concerning at the beginning of the fruiting season [21], it is essential to understand these transcriptomic differences between SM and WM, to develop management practices targeted at WM flies and therefore reduce the impact of the winter survivors on the first fruits.…”
Section: Transcriptomic Changes Underlying Cold Adaptation and Survivalmentioning
confidence: 76%
“…Additionally, monitoring traps are less efficient during the winter, which could be associated with differences in the response to volatiles between SM and WM [55]. Schwanitz et al (2022) found several differentially expressed genes between SM and WM associated with the olfactory behavior of D. suzukii, namely those linked to food-seeking and mating behaviors, reinforcing previous work that suggested that WM flies have different food preferences than SM [56,57]. Considering that the flies surviving the winter are the most concerning at the beginning of the fruiting season [21], it is essential to understand these transcriptomic differences between SM and WM, to develop management practices targeted at WM flies and therefore reduce the impact of the winter survivors on the first fruits.…”
Section: Transcriptomic Changes Underlying Cold Adaptation and Survivalmentioning
confidence: 76%
“…trapping data for the northeast USA show very few captures of D. suzukii adults during the winter compared with those during summer months [62], which is a pattern that could be due to lower population sizes but also to lower adult activity and a lack of response to volatile cues from traps by the winter compared with that of the summer morphs [63]. Nevertheless, we expect that greater numbers of overwintering D. suzukii adults could result in larger populations in the spring because of a greater likelihood of overwinter survival, leading to earlier trap captures, in contrast with Briem et al [64].…”
Section: Plos Onementioning
confidence: 92%
“…Adults of the winter phenotype have a longer lifespan at lower temperatures, have larger and darker bodies (Shearer et al., 2016; Wallingford & Loeb, 2016) and enter a temperature‐dependent reproductive diapause (Rossi‐Stacconi et al., 2016; Toxopeus et al., 2016; Zerulla et al., 2015). Furthermore, comparisons of the two phenotypes showed that the winter phenotype has an overexpression of detoxification genes in response to insecticides (Seong et al., 2022) and the summer morphs have a higher attraction to food odours (Schwanitz et al., 2022). The winter phenotype is adapted to colder conditions and is, therefore, the dominant phenotype at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%